PENGARUH INSENTIF PAJAK, GROWTH OPPORTUNITY, DAN LEVERAGE TERHADAP KONSERVATISME AKUNTANSI - INDRA IMAN SUMANTRI (Jurnal Ilmiah Akuntansi Universitas Pamulang, 2018)
The Purpose of this research is to analysis and to find the effect of Tax Insentif, Growth Opportunity, and Leverage to Accounting Conservatiesme on manufacture company at Indonesia Derivatif Exchange (IDX) in years periode 2009-2015. Tax Insentif indikator in this research using Tax Planning Policy, Growth Opportunity indicator in this research using the formula which the outstanding shares multiply closing prices on market and the result devided by Total Equities, Leverage indicator in this research using the formula which the total of Debt devided by Total Equities, and Accounting Conservatiesme indicator in this research using  acrual acumulation. This Research use  purposive sampling method, 7 company as samples are final datas using this research, it are from 37 company listed in industrial and consummer sector at Indonesia Derivatif Exchanges as population. SPSS ver 22 software use to analysis datas. The result of the research shows that Tax insentif and Growth Oppertunity effect to accounting conservatiesme and Leverage is not effect to accounting conservatieme.